Are Domestic Tourists Satisfied with the Service Quality of Travel Agencies in Kathmandu? - Shrestha, Urusha (Nepalese Journal of Hospitality and Tourism Management, 2025)
In view of the important role service quality plays in customer satisfaction this paper aimed to examine the relationship between domestic tourists’ satisfaction with service quality of travel agencies in Kathmandu. Descriptive as well as causal comparative research design was adopted. The research was administered to 120 respondents using purposive sampling technique. The findings of this research were based upon the primary survey. The paper shows that out of five hypotheses there is no significant impact of tangibility on customer satisfaction whereas reliability, responsiveness, assurance and empathy have a significant impact on customer satisfaction. This study contributes invaluable information for both academician sand managers for their theoretical and practical purposes.